(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The field of secure digital communication and data security has placed significant emphasis on the issue of image encryption. The present work introduces a unique methodology for improving image encryption by utilizing the Advanced Encryption Standard (AES) cipher in the Electronic Codebook (ECB) mode. The suggested methodology leverages the inherent resilience of AES while integrating a novel DNA-segment-based augmentation to reinforce the encryption process. This technique aims to mitigate the constraints associated with the Electronic Codebook (ECB) mode in picture encryption, with the ultimate goal of attaining an elevated standard of security and confidentiality. The efficacy of the suggested methodology is assessed through extensive experimentation, illuminating its potential to offer a sophisticated kind of image encryption that is well-suited for contemporary data security concerns.